2016
DOI: 10.1177/1087054716659360
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Impairment in Childhood ADHD: Validation of the Parent and Teacher ADHD-FX Rating Scale in a Dual-Site Clinical Sample

Abstract: Results extend upon previously published psychometric analyses to suggest that the ADHD-FX is a reliable and valid measure for parents and teachers to assess functional impairment related to ADHD (i.e., difficulties with academic achievement, social competence, and familial relationships) in community and clinical populations. Clinical implications and future directions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Examples of items assessing impairment in the home setting, in the school setting, and with peers, respectively, include “[child] doesn’t effectively complete home routines/tasks (e.g., the morning routine, chores),” “[child] doesn’t pay attention to, follow, and/or obey teacher instructions,” and “[child] doesn’t respect peers’ personal space.” An overall impairment score, as well as three subscale scores for school, home, and peers may be created. The Spanish language version of the parent ADHD-FX Scale, which was completed by parents, has been shown to have adequate reliability, divergent and convergent construct validity, and cultural properties (Haack, Gonring, Harris, Gerdes, & Pfiffner, 2019). Teachers completed the English language version of the teacher ADHD-FX Scale (Haack et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of items assessing impairment in the home setting, in the school setting, and with peers, respectively, include “[child] doesn’t effectively complete home routines/tasks (e.g., the morning routine, chores),” “[child] doesn’t pay attention to, follow, and/or obey teacher instructions,” and “[child] doesn’t respect peers’ personal space.” An overall impairment score, as well as three subscale scores for school, home, and peers may be created. The Spanish language version of the parent ADHD-FX Scale, which was completed by parents, has been shown to have adequate reliability, divergent and convergent construct validity, and cultural properties (Haack, Gonring, Harris, Gerdes, & Pfiffner, 2019). Teachers completed the English language version of the teacher ADHD-FX Scale (Haack et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a culturally sensitive measure of ADHD-related functional impairment has been developed and validated specifically for use with Latinos (Haack & Gerdes, 2016;. Early research found no significant relationships between the ADHD Functional Impairment Scale (ADHD-FX Scale) and Anglo or Latino acculturation, suggesting the appropriateness of this measure as part of a comprehensive ADHD assessment for Latino youth (Haack & Gerdes, 2016). …”
Section: Us Latino Youthmentioning
confidence: 99%
“…It has demonstrated adequate reliability and convergent and divergent validity. 25 ADHD Impact Module-Child (AIM-C)…”
Section: Coas Evaluating Additional Conceptsmentioning
confidence: 99%
“…For purposes of the current study, a mean was computed for parent-report of functional impairment in the home and for teacher-report of functional impairment at school, with higher scores representing greater impairment. It is normed for youth aged 5 to 15 years and demonstrates sound psychometrics for both the English version (completed by teachers) and Spanish version (completed by parents; Haack, Gonring, Harris, Gerdes, & Pfiffner, 2016). In the current study, the measure displayed good reliability for parent-reported home impairment (Cronbach's α = .95) and teacher-reported school impairment (Cronbach's α = .94).…”
Section: Adhd-fx Scalementioning
confidence: 99%